2011
DOI: 10.1177/1010539510393725
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Biomarkers of Stress Among Teachers in an Urban Setting

Abstract: The aim of this study was to determine the prevalence of job stress among secondary school teachers using Karasek Job Content Questionnaire (JCQ), the association between salivary cortisol, salivary IgA, and sociodemographic characteristics, and the association between log cortisol, IgA levels, and job strain categories. A cross-sectional study was undertaken using JCQ and salivary cortisol and IgA samples. Cluster sampling was done yielding 302 respondents. The prevalence of stress among all teachers was 20.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Interestingly, the results suggest a significant interactive effect of teaching years of experience with supervisor support and difficult relations. Inexperienced teachers appear to benefit more from supervisor support than their experienced colleagues, similar to results obtained by Masilamani et al, . The interactive effect of experience and supervisor support may be due to the fact that less experienced teachers may be overwhelmed by administrative duties of various kinds (Masilamani et al, ; Song, ).…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, the results suggest a significant interactive effect of teaching years of experience with supervisor support and difficult relations. Inexperienced teachers appear to benefit more from supervisor support than their experienced colleagues, similar to results obtained by Masilamani et al, . The interactive effect of experience and supervisor support may be due to the fact that less experienced teachers may be overwhelmed by administrative duties of various kinds (Masilamani et al, ; Song, ).…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, Miyazaki and colleagues reported that high-social support was directly related to NK cell levels ( 33 ). On the contrary, it is generally known that (1) job stress could be reduced by social support ( 35 ); (2) high supervisory support could decrease job stress in nurse aids ( 36 ); and (3) lower log salivary IgA levels was reveled in teachers without supervisory support ( 37 ), but our results showed that head nurse (supervisor) social support caused low-immune function by NK cell (CD56) and NK cell activity. These conflicting findings are assumed to be due to bilaterality in social supports; thus, a systematic approach to the immunological harmful effects of excessive support from a supervisor is needed in future studies.…”
Section: Discussioncontrasting
confidence: 70%
“…Teaching is one of the most stressful occupations (Gold & Roth, ; Johnson et al., ; Shen et al., ) in both western countries (Kyriacou, ; Lambert & McCarthy, ; McCarthy, Lambert, Lineback, Fitchett, & Baddouh, ; McCarthy, Lambert, & Reiser, ) and eastern countries, such as Singapore (Chan, Lai, Ko, & Boey, ), Malaysia (Masilamani et al., ), and China (Wang et al., ; Yong & Yue, ; Zhang, Bian, & Dong, ). According to one prominent stress theory, namely the transactional model of stress and coping, stress occurs as a result of an imbalance between perceived demands and perceived capability or resources to cope with those demands (Lazarus & Folkman, ).…”
Section: Classroom Appraisal Of Resources and Demandsmentioning
confidence: 99%